1981
DOI: 10.1111/j.1600-0447.1981.tb00710.x
|View full text |Cite
|
Sign up to set email alerts
|

Central pre‐ and postsynaptic monoamine receptors in antidepressant therapy

Abstract: Activation of postsynaptic noradrenergic al-receptors may be involved in the mediation of psychomotor activating effects of tricyclic antidepressant (TCA) drugs. On the other hand, the pronounced sedative properties of some TCA drugs seem to be correlated with their u,-receptor blocking capacity. The presynaptic u2-receptors probably mediate the feed, back inhibition of central NE neurons seen after administration of TCA drugs, particularly the secondary amines. Yet other antidepressants such as mianserin are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This indicates that ǃ2 stimulation produces antidepressant effect. Reduced central ǃ-receptor activation may contribute to depressive symptoms associated with ǃ-adrenergic blocking drugs [71]. In the forced swimming test, it was found that isoprenaline increases the duration of immobility, while salbutamol decreases it [72].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that ǃ2 stimulation produces antidepressant effect. Reduced central ǃ-receptor activation may contribute to depressive symptoms associated with ǃ-adrenergic blocking drugs [71]. In the forced swimming test, it was found that isoprenaline increases the duration of immobility, while salbutamol decreases it [72].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that β2 stimulation produces antidepressant effect. Reduced central β-receptor activation may contribute to depressive symptoms associated with β-adrenergic blocking drugs [71]. In the forced swimming test, it was found that isoprenaline increases the duration of immobility, while salbutamol decreases it [72].…”
Section: Discussionmentioning
confidence: 99%
“…As concerns locus coeruleus neurons, presynaptic c~2-adrenoceptors probably mediate the feedback inhibition seen after acute administration of tricyclic antidepressants (Svensson et al, 1981). However, somatodendritic 5-HT 1 autoreceptors could mediate the feedback inhibition of dorsal raphe neurons (Blier and De Montigny, 1994).…”
Section: Discussionmentioning
confidence: 99%